ETHICAL CONSUMERS IN GREECE: WHO ARE THEY? - Delistavrou, Antonia; Katrandjiev, Hristo; Tilikidou, Irene (Annals of Spiru Haret University. Economic Series, 2017)
Presents a segmentation on the basis of the overall ethical consumption concept for the first time in Greece. Four segments were identified: Ethical Consumers (18.09%), Boycotters (20.48%), Ecological Consumers (27.86%) and Conventional Consumers (33.57%). The Ethical Consumers’ segment consists of well educated citizens, who adopt all ethical behaviours more frequently. These consumers were found to be more confident they can control politics, less materialists, most attracted by post-materialist goals as well as less sceptical towards ethical products and less indifferent about ethical consumption issues. This segment may be considered as attractive enough to be targeted by business and non for profit organisations.